Sustainable Pathways to Quality: Exploring SDG 4’s Influence on Higher Education Transformation in Pakistan - Sain, Zohaib Hassan; Abdullah, Nurulannisa Binti; Hidayat, Muhammad Taufik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to explore the practice of continuing education in higher education institutions in Pakistan, focusing on implementing the Sustainable Development Goal (SDG) 4. Using a qualitative approach and case study methods, data were collected through in-depth interviews with department heads, lecturers, and students and analysis of curriculum documents from four public universities in Lahore. The results show a significant gap between the existing curriculum content and the actual needs in the job market, where many curricula still need to be focused on theoretical knowledge with adequate attention to the development of practical skills necessary to face the challenges of the professional world. This research identifies the need for curriculum updates, lecturer training, and improvement of educational facilities to build graduates who are better prepared to face global demands. The implications of these findings emphasize that reforms in higher education are urgently needed to ensure that the curriculum offered is relevant and, by the demands of the industry, to create quality and highly competitive human resources in the global market.